2001
DOI: 10.1002/ijc.1404
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects ofc-myc and Epstein-Barr virus latent genes on the phenotype of human B cells

Abstract: Epstein-Barr virus (EBV) immortalized cells and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 26 publications
9
52
0
Order By: Relevance
“…A similar negative effect of LMP1 on c-myc in U2932 LMP1 expressors was observed by us (data not shown). Overall, these data are consistent with the previously described incompatibility between the latency III-driven transcription program and c-myc-driven growth program (Pajic et al, 2001), and suggest that such an incompatibility might be due to differential and opposite regulation of the same miRs by c-myc and LMP1. Although further studies will be required to investigate how LMP1 downregulates c-myc and consequently alters miR expression, we would like to propose a scenario of oncogene cooperation in which suppression of miR-29b by c-myc (Chang et al, 2008) and the consequent positive regulation of TCL1 might be of critical significance in the pathogenesis of B-cell lymphomas with high c-myc and TCL1 expression.…”
Section: Discussionsupporting
confidence: 91%
“…A similar negative effect of LMP1 on c-myc in U2932 LMP1 expressors was observed by us (data not shown). Overall, these data are consistent with the previously described incompatibility between the latency III-driven transcription program and c-myc-driven growth program (Pajic et al, 2001), and suggest that such an incompatibility might be due to differential and opposite regulation of the same miRs by c-myc and LMP1. Although further studies will be required to investigate how LMP1 downregulates c-myc and consequently alters miR expression, we would like to propose a scenario of oncogene cooperation in which suppression of miR-29b by c-myc (Chang et al, 2008) and the consequent positive regulation of TCL1 might be of critical significance in the pathogenesis of B-cell lymphomas with high c-myc and TCL1 expression.…”
Section: Discussionsupporting
confidence: 91%
“…In the cell system from which the P4936 cell line is derived, c-Myc overexpression has earlier been shown to c-Myc and the germinal center program in BL H Scheller et al induce some markers that are also found on GC cells but are negatively affected by EBV latent genes (Polack et al, 1996;Pajic et al, 2001). We, therefore, assessed whether c-Myc overexpression is also capable of inducing expression of the centroblast marker CD77.…”
Section: Resultsmentioning
confidence: 95%
“…Although earlier studies showed high c-Myc expression in the GC, more recent data revealed that c-Myc expression and activity in GC B cells are rather uncharacteristically low (MartinezValdez et al, 1996;Shaffer et al, 2001;Klein et al, 2003). In vitro models of BL pathogenesis have shown, though, that c-Myc overexpression in B cells may induce some features that are also found in GC B cells (Polack et al, 1996;Pajic et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…15 Activation of EBNA2 causes a change of the viral transcription program, followed by a shift from the group I to the group III BL phenotype, which renders the cells TGF-␤-resistant.…”
Section: Tgf-␤ Can Readily Induce Junb and Id3 Expression In Myc-and mentioning
confidence: 99%
“…The P493-6 cell line can, however, reactivate the lymphoblastoid, group III phenotype of the parental LCL upon addition of estrogen to the cell culture medium. 15 Thus, in contrast to previous results, the P493-6 cell line offers the unique option of studying epigenetic changes when proliferation is driven either by EBNA2 or by Myc on the isogenetic background of a single cell line.…”
mentioning
confidence: 93%